IMPLEMENTATION OF INTERNET OF THINGS (IoT) BASED ON GOOGLE SHEETS FOR WATER QUALITY MONITORING SYSTEM - Pebralia, Jesi; Handayani, Linda; Suprayogi, Dawam; Amri, Iful (JOURNAL ONLINE OF PHYSICS, 2023)
Temperature, pH, and TDS are important indicators of water quality that affect various aspects. This research aims to develop a water quality monitoring system by implementing Internet of Things (IoT) technology based on Google Sheets. Based on the tests for each sensor - temperature, pH, and TDS - the results show that the system has an excellent level of measurement precision, with an average precision value of above 95%. The findings also indicate that Google Sheets can be utilized in IoT technology and can operate on more than one distinct computer device at the same time. The use of Google Sheets in IoT technology is highly effective, flexible, and user-friendly. The measured data can be automatically stored and can be visualized effectively.".